Jenis Masker, Durasi Penggunaan Masker dan Body Mass Index (BMI) terhadap Kejadian Acne Vulgaris - Zufara, Iffa Maulida; Prakoeswa, Flora Ramona Sigit (Journal of Telenursing (JOTING), 2023)
This study aims to see the relationship between type of mask, duration of mask use, and Body Mass Index (BMI) on the incidence of Acne Vulgaris (AV). The method used is an observational analytical research design with a cross-sectional approach. The research results showed that the majority were female, 71.1%. Most sample data that experienced AV was also obtained at 92.2%. Most presentations occurred in women who experienced AV in this study, amounting to 64.8%. The statistical test results showed that the three variables had a p-value > 0.05. In conclusion, no significant relationship exists between the type of mask, duration of mask use, and Body Mass Index (BMI) with the incidence of Acne Vulgaris in FK UMS students. Keywords: Acne Vulgaris, BMI, Body Mass Index, Duration of Mask Use, Type of Mask